Lectin pathway effector enzyme mannan‐binding lectin‐associated serine protease‐2 can activate native complement C3 in absence of C4 and/or C2. Issue 5 (10th February 2017) - Yaseen, Sadam; Demopulos, Gregory; Dudler, Thomas; Yabuki, Munehisa; Wood, Christi L.; Cummings, W. Jason; Tjoelker, Larry W.; Fujita, Teizo; Sacks, Steven; Garred, Peter; Andrew, Peter; Sim, Robert B.; et al.
ABSTRACT: All 3 activation pathways of complement—the classic pathway (CP), the alternative pathway, and the lectin pathway (LP)— converge into a common central event: the cleavage and activation of the abundant third complement component, C3, via formation of C3‐activating enzymes (C3 convertases). The fourth complement component, C4, and the second component, C2, are indispensable constituents of the C3 convertase complex, C4bC2a, which is formed by both the CP and the LP. Whereas in the absence of C4, CP can no longer activate C3, LP retains a residual but physiologically critical capacity to convert native C3 into its activation fragments, C3a and C3b. This residual C4 and/or C2 bypass route is dependent on LP‐specific mannan‐binding lectin‐associated serine protease‐2. By using various serum sources with defined complement deficiencies, we demonstrate that, under physiologic conditions LP‐specific C4 and/or C2 bypass activation of C3 is mediated by direct cleavage of native C3 by mannan‐binding lectin‐associated serine protease‐2 bound to LP‐activation complexes captured on ligand‐coated surfaces.—Yaseen, S., Demopulos, G., Dudler, T., Yabuki, M., Wood, C. L., Cummings, W. J., Tjoelker, L. W., Fujita, T., Sacks, S., Garred, P., Andrew, P., Sim, R. B., Lachmann, P. J., Wallis, R., Lynch, N., Schwaeble, W. J. Lectin pathway effector enzyme mannan‐binding lectin‐associated serine protease‐2 can activate native complement C3 in absence of C4 and/or C2. FASEB J. 31, 2210–2219 (2017). www.fasebj.org